Identifying Student Motivation in Learning Islamic Education in Senior High School - Saputri, Teni Eki; Izmi, Nelly; Putera, Odsisa; Irayanti, Irma (Ahlussunnah: Journal of Islamic Education, 2022)
In general, the reality that with a Senior High School ll number of teachers and a large number of students is that it is unlikely that teachers will be able to provide maximum motivation to students. A large number of students, not comparable to the number of teachers, will usually have difficulty nurturing students with maximum motivation. The aim of this research is to look at students' intrinsic motivation, students' extrinsic motivation, supporting and inhibiting factors in learning Islamic religious education. This research uses descriptive qualitative methods. The data collection techniques used are observation, interviews, and documentation with data analysis through data reduction, data presentation, and drawing conclusions and verification. The results of this research were obtained: i) the intrinsic motivation of students at Senior High School 2 Payakumbuh in learning Islamic religious education was obtained through the appreciation given by the teacher and the students' sense of responsibility. This award is motivation for students to develop and progress further in their learning process, ii) extrinsic motivation for Senior High School 2 Payakumbuh students is obtained from the motivation provided by teachers, principals, and all the environment in the school. Adequate infrastructure is one of the motivations for student learning in achieving goals, iii) supporting factors in increasing student learning motivation in learning Islamic religious education, namely students are given Islamic religious learning guidance, in the form of congregational prayers, tahfiz, reading the koran and delivering learning material. The inhibiting factor in increasing students' learning motivation in learning Islamic religious education is the lack of Islamic religious education lesson hours at school. Apart from the lack of teaching hours for Islamic religious education teachers, students who study religion are less aware of the importance of studying Islam. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.